Znaczenie żywności funkcjonalnej, nutraceutyków, w tym astaksantyny w żywieniu człowieka - Lis, Kinga; Kołoczek, Henryk (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2020)
Nutrition plays an extremely important role in maintaining proper body condition and human health. Nevertheless, many bad eating habits related to work mode, constant rush or stress are observed. These factors contribute to the serious civilization diet-related diseases, among which the most severe are: diabetes, cardiovascular disease or tumor. However, the problem is not only being countered by constant development in both the food and pharmaceutical sectors, but also nutraceuticals and functional foods. These products are on the borderline between pharmaceuticals and food products, and their role is to enable the use of valuable bioactive compounds contained in food. One of the most valuable nutraceutical is astaxanthin, which is now considered to be the strongest known antioxidant. Its incomparably high antioxidant activity underpins a wide range of applications, the most important of which concern human health. Astaxanthin’s health-promoting properties include anti-inflammatory, anti-aging and anticancer properties. Astaxanthin also plays a significant role in treatment and prevention of diabetes (with particular attention to type II diabetes), neurodegenerative and cardiovascular diseases. The interest in astaxanthin is constantly growing, and new possibilities of its acquisition and application are being researched by scientists. More and more attention is directed towards astaxanthin obtained from Phaffia rhodozyma yeast, and new products containing yeast astaxanthin are being introduced. Growing interest in astaxanthin is also visible on world markets. The aim of this work is to present astaxanthin as a functional food ingredient, and to draw the reader’s attention to its enormous application potential to fight against diet-related diseases.
Keywords: nutraceuticals; functional foods; astaxanthin; diet-related diseases